Designing, manufacturing robot for climbing walls and ceilings - Huỳnh Nguyễn Hoàng; Hồ Minh Phương (Journal of Technical Education Science, 2012)
In design and manufacture research of mobile robot with capable of climbing stick on walls and ceilings, the biggest challenge is set robot must be able to cling with the wall for cracks or small gaps, not dirty walls, can stick on the different surfaces. With these challenges is the commonly used methods such as vacuum aspiration, using glue or other adhesive to stick, simulating biological from climbing animals, using techniques of magnet... can not respond. So the main objective of the project is to research the design and manufacture of wall climbing robots using non-contact suction method. The main contents of this method using air source is supplied from the compressor, run through the suction mechanism is designed to speed up the air flow velocity is very high and thus will create low pressure areas can adhesion the wall. This method can solve the problems and challenges mentioned.